2016
DOI: 10.1016/s2213-2600(16)30081-9
|View full text |Cite
|
Sign up to set email alerts
|

The nasal microbiota in infants with cystic fibrosis in the first year of life: a prospective cohort study

Abstract: Swiss National Science Foundation, Fondation Botnar, the Swiss Society for Cystic Fibrosis, and the Swiss Lung Association Bern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 31 publications
4
65
1
2
Order By: Relevance
“…Nevertheless, a significant effect of season on the microbiota was observed in the human-derived sample types from pig and cow farmers but not nonexposed individuals. In young children and adults, it has also been shown that season acts as a major factor in driving the dynamics of the nasal microbiota (25,28). In contrast to our findings, De Boeck et al reported no correlation between season and microbial composition in healthy humans (29).…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, a significant effect of season on the microbiota was observed in the human-derived sample types from pig and cow farmers but not nonexposed individuals. In young children and adults, it has also been shown that season acts as a major factor in driving the dynamics of the nasal microbiota (25,28). In contrast to our findings, De Boeck et al reported no correlation between season and microbial composition in healthy humans (29).…”
Section: Discussioncontrasting
confidence: 99%
“…It does, however, contrast with the findings of previous longitudinal analyses of children with CF, which only examined the upper airway microbiota 10 28–32. During infancy, the nasopharyngeal microbiota is dynamic,33–35 although differences between that of infants with CF and healthy controls have been reported,30 31 including increased relative abundance of Staphylococcae at baseline,31 changes in Staphylococcus species,31 and the emergence of gram-negative bacteria30 following antibiotic exposure. Two smaller studies examining oropharyngeal swabs from infants29 and children10 with CF suggested that upper airway microbial diversity increased with age.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic diseases affecting mucociliary clearance, such as cystic fibrosis and primary ciliary dyskinesia, affect the URT microbiota. Two recent studies have identified that infants with cystic fibrosis, which results in a thickened mucus layer, have an altered URT microbiota development compared to healthy infants including increased relative abundance of Staphylococcus species and decreased abundance of potential beneficial bacteria . Many people with primary ciliary dyskinesia, a combination of diseases resulting in decreased ciliary action to clear mucus, also suffer from chronic rhinosinusitis, and there is a high reported rate of URT manifestations of disease, contributing to morbidity .…”
Section: Factors Affecting Urt Microbiotamentioning
confidence: 99%